Collective Short-Time Dynamics in Polymer Melts: Two-Step Quenches and Spinodal Decomposition - Steffen, David; Rottler, Jörg; Müller, Marcus (Macromolecules, 2025)
In polymer melts, the segmental density does not simply relax diffusively due to intramolecular dynamics on short time scales. Using particle-based simulations of a highly coarse-grained polymer model, we explore the collective short-time dynamics under two distinct scenarios: (i) noninteracting polymer chains subject to a two-step change of an external field and (ii) phase separation due to attractive interactions. In the case of the two-step external field, we observe a nonmonotonic relaxation behavior of a collective density modulation, while for the case of the spontaneous growth of density modulations in response to the introduction of attractive interactions (spinodal decomposition), we observe an initial nonexponential growth on very short time scales, followed by a transition to exponential growth. We show that these effects can be captured by linear response theory, in contrast to dynamic self-consistent field theory (D-SCFT) that always predicts a slow exponential relaxation of segmental density modes. The short-time deviations from D-SCFT stem from two key characteristics: (i) the molecular configurations are not in equilibrium with the instantaneous density field, and (ii) the segmental dynamics display subdiffusive behavior.